Architectural Language Based on ‘Place’: The Case of Sille - Kuyrukçu, Emine Yıldız; Kuyrukçu, Zafer (International Journal of Natural Sciences Research, 2015)
The design studio is a medium of intense learning in architectural education. The theme of the studio exercise presented in this paper consists of the comprehension of place and space qualities and proposing new design in a historic context. While this theme directed learning of pertinent design vocabulary and concepts, it also required that students should develop an ethical approach based on the sense of responsibility towards delicate environments possessing cultural heritage. The aim of this study is to make the architect candidates do the investigation related to the “place”, and live the experience of using the properties unique for the place as design criteria. Konya-Sille, which for some people it is a Byzantium village, for some other it is a Central Anatolian settlement dated to very old periods, where either Byzantines or Turks, as being Orthodox Christian and Muslim, lived together. Sille, with it’s economic potential, has became one of the most important economic centers of Konya and it’s environment. Sille, which is known a very important centre up to the end of 19 Century, fell into a declining period at the end of that century, and accelerated its speed during the Post Exchanging period realized together with Lausanne Agreement, and reached to the 21 Century. The design problem is determined as “cultural center” in this area where is under conservation and has a unique traditional texture. In this study about a studio experience; the process of the discussions on culture, history, religion, texture, tradition, originality, continuity concepts upon context/place and new design realization in an existing texture in the direction of these concepts are explained.